2005
DOI: 10.1097/01.ccm.0000171538.61759.09
|View full text |Cite
|
Sign up to set email alerts
|

Post-thrombolysis intracerebral hemorrhage: Data from the Spanish Register ARIAM*

Abstract: Factors associated with the development of ICH in our population were age and arterial hypertension, whereas smoking and the administration of b-blockers or ACE inhibitors were associated with a reduction in incidence. Among patients with AMI complicated by ICH, mortality was associated with age, arterial hypertension, cardiopulmonary resuscitation, and the use of mechanical ventilation, whereas the administration of oral b-blockers and ACE inhibitors could be associated with a reduction in mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
9
1
Order By: Relevance
“…Thus, if anything, our analysis underestimates the incidence as compared with clinical studies and registries,17 which have used different definitions of major bleeding, including various levels of drop in haemoglobin or haematocrit 18. Intracranial bleeding complications of 0.8% in this study seem to be in line with previously published data from both clinical trials1 13 14 and registers 6–8 19…”
Section: Discussionsupporting
confidence: 85%
“…Thus, if anything, our analysis underestimates the incidence as compared with clinical studies and registries,17 which have used different definitions of major bleeding, including various levels of drop in haemoglobin or haematocrit 18. Intracranial bleeding complications of 0.8% in this study seem to be in line with previously published data from both clinical trials1 13 14 and registers 6–8 19…”
Section: Discussionsupporting
confidence: 85%
“…According to several previous studies, the major drawback of CDT therapy is hemorrhagic complications, which have been related to prolonged treatment duration. 13,25 In our study, we did not observe any major bleeding complications, probably due to the small sample size, a shorter thrombolysis time compared with previous studies, and the daily measurement of the fibrinogen level. In addition, Yang et al 16 reported that patients with acute iliofemoral deep venous thrombosis who underwent PMT using AngioJet had an increased risk of postoperative acute kidney injury (AKI) compared with those who underwent CDT.…”
Section: Discussioncontrasting
confidence: 57%
“…In many studies, the major drawback of CDT therapy has been hemorrhagic complications, which have been related to prolonged treatment duration (17)(18)(19)(20)(21)(22)(23). Our CDT patients received a median of 21 hours' infusion of the thrombolytic agent, as opposed to 20 minutes in PMT patients.…”
Section: Kim Et Al Compared Cdt and Pmt In The Treatment Of 23 Uedvtmentioning
confidence: 99%